Just war; unjust consequences. A comparative analysis of the Christian realist tradition in St. Augustine and Reinhold Niebuhr with U.S. foreign policy in Iraq - De Villiers, D.E. (Dawid Etienne) (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2014